The Rise and Fall of the Religious Left: Politics, Television, and Popular Culture in the 1970s and Beyond - Rolsky, L. Benjamin (Columbia Series on Religion and Politics, 2019)
L. Benjamin Rolsky examines the ways in which American liberalism has helped shape cultural conflict since the 1970s through the story of how television writer and producer Norman Lear galvanized the religious left. He foregrounds the roles played by popular culture, television, and media in America's religious history.